COVID-19 Vaccination and the Rate of Immune and Autoimmune Adverse Events Following Immunization: Insights From a Narrative Literature Review - Mahroum, Naim; Lavine, Noy; Ohayon, Aviran; Seida, Ravend; Alwani, Abdulkarim; Alrais, Mahmoud; Zoubi, Magdi; Bragazzi, Nicola Luigi (Frontiers in Immunology, 2022)
Despite their proved efficacy and huge contribution to the health of humankind; vaccines continue to be a source of concern for some individuals around the world. Vaccinations against COVID-19 increased the number of distressed people and intensified their concerns, particularly as the pandemic is still emerging and the populations were encouraged to be vaccinated under various slogans like “back to normal life” and “stop coronavirus”, which is still to be achieved. As fear of vaccination-related adverse events is the main reason for vaccine hesitancy, we viewed autoimmune side effects in particular, though very rare, as the most worrisome aspect of the vaccines. Among others, autoimmune adverse events of the currently circulating COVID-19 vaccines include neurological ones such as Guillain-Barre syndrome, transverse myelitis, and Bell’s palsy. In addition, the newly introduced notion related to COVID-19 vaccines, “vaccine-induced immune thrombotic thrombocytopenia”, and myocarditis, are of importance as well. Reviewing recent medical literature while focusing on the listed autoimmune side effects, demonstrating their rate of occurrence, presenting the cases reported, and their link to the specific type of COVID-19 vaccines formed the aim behind our review. In our paper we illustrate the different vaccine types in current use, their associated autoimmune side effects, as well as focus on the adverse events of the 3 main COVID-19 vaccines (BNT162b2, mRNA-1273, and ChAdOx1). While the rate of such side effects is extremely low, addressing the issue in this manner, in our opinion, is the best strategy for coping with vaccine hesitancy.